Raman studies on zoisite and tanzanite for gemmological applications. (13th July 2021) - Coccato, Alessia; Bersani, Danilo; Caggiani, Maria Cristina; Mazzoleni, Paolo; Barone, Germana
Abstract: Tanzanite is the blue to violet‐blue variety of the sorosilicate zoisite; its colour is due to vanadium substitution of aluminium in the octahedral sites and is proved to appear after natural or artificial heating to approximately 500°C. Its colour makes it a highly appreciated gemstone, for this reason often imitated or thermally treated with the aim of enhancing its hue. Tanzanite loose gemstones are easily identified by classical gemmology methods that are not always applicable to mounted jewels. At the same time, zoisite Raman spectra are rarely reported in literature and never with a systematic approach. In this work, zoisite samples and cut tanzanite gemstones were considered, with the aim of filling this gap by addressing different methodological aspects. Namely, the orientational effects were investigated to explain the spectral variability, the photoluminescence bands were differentiated from the Raman signals using different excitation wavelengths, and the effectiveness of portable instrumentation in the correct identification of tanzanite was evaluated. The results are encouraging, showing that zoisite is revealed, notwithstanding orientational effects, by both portable and laboratory Raman instruments with comparable performances, opening the way to an effective identification of mounted tanzanite gemstones. Furthermore, the employ of different excitation wavelengths allowed to distinguish the photoluminescence bands with both categories of devices, thus identifying rare earth elements (REEs) likely associated with the mineral's genesis. Abstract : Raw zoisite and cut tanzanite samples were systematically analysed by Raman spectroscopy. Orientational effects were described to explain spectral variability. Portable and laboratory instruments with different lasers were tested to differentiate photoluminescence contributions and to evaluate the effectiveness of mobile devices for mounted tanzanite identification.